Analisis Penanganan Cargo High Temperature pada Pemuatan Batubara MV. WEI LUN JU LONG di Kaliorang Anchorage - Dimas Dzaky Djauhari; Femmy Asdiana; Romanda Annas Amrullah (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Coal loading activities to ships must prioritize Safety factors according to applicable regulations. However, Coal Cargo was found that did not comply with the loading rules, namely there was a point where the Coal Cargo was located on the barge with a Temperature of more than 55°C, so that the Cargo could not be loaded onto the ship. The purpose of this study was to deterMine the requirements for safe Coal Cargo and according to procedures for loading, and how to handle High Temperature Coal Cargoes. The research method used is descriptive qualitative which describes the Handling High Temperature Cargo in Coal Loading MV. WEI LUN JU LONG at Kaliorang Anchorage. Data collection techniques through observation, literature study, documentation, and interviews. The results of this study indicate that the requirements for safe Coal Cargo and according to procedures for loading in the hold are the Temperature of the Coal Cargo not more than 55°C and the actual water content value not Higher than the TML, as well as the method of handling High Temperature Coal Cargo, namely by trimming Coal Cargo on barges or by replacing Cargo with Cargo on other barges. The advice given is to prepare a good load and according to the rules for loading, to prepare the completeness of equipment, and personal protective equipment if problems occur and handling is needed, and to improve good working relationships with each other.